2015
DOI: 10.1159/000437210
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disturbance and the Bizarre: On Incomprehensibility in Schizophrenic Delusions

Abstract: The notion of ‘bizarre delusion' has come into question in contemporary anglophone psychopathology. In DSM-5, it no longer serves as a special criterion for diagnosing schizophrenia nor as an exclusion criterion for delusional disorder. Empirical studies influencing this development have, however, been relatively sparse and subject to methodological criticism. Major reviews have concluded that current conceptualizations of bizarre delusions may require rethinking and refinement. Defining bizarreness entails a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…A recent study (Lebedev et al 2015) found that individual variability of psilocybin-induced psychedelic symptoms was best explained by a common factor that included vivid dreamlike imagery, loss of self-boundaries and fear of losing control over thought processes. Moreover, there is evidence that bizarreness in REM dreams of normal subjects (Fosse et al 2004) and in waking thoughts and dreams of schizophrenic patients (Rasmussen and Parnas 2015, Sass and Byrom 2015, Scarone et al 2008, Limosani et al 2011 is closely related to disturbed sense of self, and there is qualitative evidence that many bizarre features of both psychedelic imagery and dreams can be traced back to loss of self-boundaries and cognitive control (Pines 1976, Leuner 1968, Savage 1955, Abramson et al 1955. For example, one subject in the present study described loss of self-boundaries and cognitive control, and how closely this was related to bizarre imagery in the LSD condition as follows: "I merged with the environment.…”
Section: Cognitive Bizarreness and Sense Of Selfmentioning
confidence: 99%
“…A recent study (Lebedev et al 2015) found that individual variability of psilocybin-induced psychedelic symptoms was best explained by a common factor that included vivid dreamlike imagery, loss of self-boundaries and fear of losing control over thought processes. Moreover, there is evidence that bizarreness in REM dreams of normal subjects (Fosse et al 2004) and in waking thoughts and dreams of schizophrenic patients (Rasmussen and Parnas 2015, Sass and Byrom 2015, Scarone et al 2008, Limosani et al 2011 is closely related to disturbed sense of self, and there is qualitative evidence that many bizarre features of both psychedelic imagery and dreams can be traced back to loss of self-boundaries and cognitive control (Pines 1976, Leuner 1968, Savage 1955, Abramson et al 1955. For example, one subject in the present study described loss of self-boundaries and cognitive control, and how closely this was related to bizarre imagery in the LSD condition as follows: "I merged with the environment.…”
Section: Cognitive Bizarreness and Sense Of Selfmentioning
confidence: 99%
“…and Byrom [40] discuss ipseity disturbance's specific relevance for understanding the distinctively "bizarre" nature of delusions in schizophrenia (and elsewhere they speculate [41] about associated neurobiological factors that may contribute to self disorder as well as to the formation and maintenance of such delusions). [45] also reported no correlation between basic self-disturbance and neurocognitive measures in a first episode schizophrenia sample and a clinical high risk for psychosis sample, respectively.…”
Section: The Phenomenological Domain: Basic Self-disturbance In Schizmentioning
confidence: 99%
“…Results from empirical studies using the EASE scale (Haug et al, ; Nelson, Thompson, & Yung, ; Nordgaard, Nilsson, Saebye, & Parnas, ; Raballo & Parnas, ; Raballo, Saebye, & Parnas, ) have now highlighted the high specificity of minimal‐self disorders in the schizophrenia spectrum, suggesting that minimal‐self disorders are trait markers of schizophrenia spectrum disorders (schizophrenia and schizotypal disorders). They would represent trait features that characterize the typical core of schizophrenia (Sass & Byrom, ).…”
Section: Schizophrenia Minimal Self and Timingmentioning
confidence: 99%